Healing the wounds of the nations: towards a common mission of the Churches 1 - Müller-Fahrenholz, Geiko (Hervormde teologiese studies, 2000)
In what ways can the Churches be - or become - healing agents for their people? The article argues that churches are communities of remembering. And as remembering centers around the Crucified, the "wounded" (H Nouwen), it becomes a remembering energy, i.e. an energy that unites what has been dismembered. It is argued that one of the most destructive aspects of contemporary societies is the "winner-syndrome". By regarding human beings as "winners" and "losers" it sets in motion merciless struggles for the "top-position" which turn out to be processes of denial and exclusion and create a downward spiral of violence. The churches' ecumenical healing ministries should begin by dismantling the matrix of denial and violence in order to create a "matrix of connectedness" that is grounded in the basic woundedness of all human beings. The author participated in the Harare Assembly of the World Council of Churches (1998) and sees his reflections as a contribution to the "Decade to Overcome Violence" which is to begin 2001.